APOE gene ɛ4 allele (388C‐526C) effects on serum lipids and risk of coronary artery disease in southern Chinese Hakka population. Issue 9 (27th July 2021) - Liu, Qinghua; Wu, Heming; Yu, Zhikang; Huang, Qingyan; Zhong, Zhixiong
Abstract: Objective: To analyze the relationship of Apolipoprotein E ( APOE ) and solute carrier organic anion transporter family member 1B1 ( SLCO1B1 ) gene polymorphisms with coronary artery disease (CAD). Methods: 1, 129 CAD patients and 1, 014 non‐CAD controls were included in the study, and relevant information and medical records were collected. The single‐nucleotide polymorphisms (SNPs) were analyzed, including rs429358, rs7412 in APOE gene and rs2306283, rs4149056 in SLCO1B1 gene. Results: The CAD patients' average age was 66.3 ± 10.7 years, while 65.5 ± 12.0 years in controls. The frequencies of APOE allele ɛ3, ɛ4, and ɛ2 were 83.01%, 10.08%, and 6.91% respectively. There were statistically significant differences in genotype ɛ3/ɛ4 (χ 2 = 8.077, p = 0.005) in CAD patients compared with the controls. The SLCO1B1 genotype *1b/*1b and haplotype *1b showed the highest frequency in the study sample. Moreover, ε4 carriers had significantly lower HDL‐C, Apo‐A1 levels than ε3 carriers among CAD patients, while ε2 carriers showed lower LDL‐C, Apo‐B level, and higher Apo‐A1/Apo‐B level than ε3 and ε4 carriers. In controls, ε2 carriers showed lower LDL‐C and Apo‐B level, higher Apo‐A1, and Apo‐A1/Apo‐B level than ε4 carriers. Logistic regression analysis showed that high LDL‐C and Apo‐B level, low HDL‐C level, smoking, and the ε4 allele were risks for the presence of CAD. Conclusions: APOE ε4 allele may be associated with susceptibility to CAD in southern Chinese Hakka population. It indicated that the APOE SNPs rs429358 and rs7412 are associated with CAD, but not SNPs rs2306283 and rs4149056 of SLCO1B1 gene. Abstract : Apolipoprotein E (ApoE) and solute carrier organic anion transporter family member 1B1 (SLCO1B1) are involved in the regulation of lipid metabolism; however, the relationship between APOE and SLCO1B1 gene polymorphisms and coronary artery disease (CAD) has been controversial. APOE ε4 allele may be associated with susceptibility to CAD in southern Chinese Hakka population. It indicated that the APOE SNPs rs429358 and rs7412 are associated with CAD. This is the first systematic study of the association between CAD and APOE and SLCO1B1 gene polymorphisms in Hakka population. This study provides valuable information for the prediction of the risk of coronary heart disease.